2021
DOI: 10.1371/journal.pone.0254996
|View full text |Cite
|
Sign up to set email alerts
|

Study of the influencing factors of the liquid CO2 phase change fracturing effect in coal seams

Abstract: To study the influence of different factors on the cracking effect of the liquid CO2 phase transition, the mechanics of coal rock crack extension based on liquid CO2 phase change blast loading were studied. Through the application of simulation software to analyze the influence of coal seam physical parameters (in situ stress, gas pressure, modulus of elasticity and strength of coal) and blasting parameters (fracturing pore size and peak pressure of detonation)on the effect of liquid CO2 phase change cracking,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…In order to better apply the liquid CO 2 phase change fracturing technology to the field of low-permeability coal seam permeability enhancement and reinforced anti-outburst field, a field test of liquid CO 2 phase change fracturing for enhanced prepumping coal seam gas through the seam was conducted in the 13th mine of Pingjiang coal mine and through the gas extraction effect after fracturing the coal seam to determine the reasonable placement of liquid CO 2 blasting holes. Jia et al 88 used LS-DYNA software to simulate and analyze the effects of physical parameters of coal seams and borehole diameter on the effect of liquid CO 2 phase change fracturing on coal seams, and the results show that there are positive relationships between the fracturing effect of coal seams and the pressure, modulus of elasticity, and borehole diameter, there are negative relationships with the geopathic stress and compressive strength, and the process is nearly irrelevant to the tensile strength. Hu et al 89 tablished a multiphysical field coupling model and found that the longer the liquid CO 2 phase transition cracking time, the greater the fracturing radius.…”
Section: Current Status Of Research On Anhydrous Coal and Gas Outburs...mentioning
confidence: 99%
“…In order to better apply the liquid CO 2 phase change fracturing technology to the field of low-permeability coal seam permeability enhancement and reinforced anti-outburst field, a field test of liquid CO 2 phase change fracturing for enhanced prepumping coal seam gas through the seam was conducted in the 13th mine of Pingjiang coal mine and through the gas extraction effect after fracturing the coal seam to determine the reasonable placement of liquid CO 2 blasting holes. Jia et al 88 used LS-DYNA software to simulate and analyze the effects of physical parameters of coal seams and borehole diameter on the effect of liquid CO 2 phase change fracturing on coal seams, and the results show that there are positive relationships between the fracturing effect of coal seams and the pressure, modulus of elasticity, and borehole diameter, there are negative relationships with the geopathic stress and compressive strength, and the process is nearly irrelevant to the tensile strength. Hu et al 89 tablished a multiphysical field coupling model and found that the longer the liquid CO 2 phase transition cracking time, the greater the fracturing radius.…”
Section: Current Status Of Research On Anhydrous Coal and Gas Outburs...mentioning
confidence: 99%
“…Then they conducted a numerical simulation of CO 2 phase change cracking. The results showed that the influence radius of cracking was 2.55-2.70 m. Jia et al [26], based on the gray correlation analysis method, the effects of different factors on the phase change cracking effect of liquid CO 2 were studied. The results showed that the phase change cracking effect of liquid CO 2 was positively correlated with the changes of gas pressure, elastic modulus, fracture hole diameter, and detonation peak pressure, and this effect was negatively correlated with the changes of in ground stress and compressive strength, and was almost independent of tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, researchers in the industry have focused on determining the factors that affect blasting cracking and nding methods to improve prediction accuracy. Jia et al [19] studied the in uence of different factors on the phase change cracking effect of liquid CO 2 based on the gray correlation analysis method. The results showed that the gas pressure and ground stress directly affected the blasting cracking effect.…”
Section: Introductionmentioning
confidence: 99%